Sensitivity of Candida albicans isolates to caspofungin – comparison of microdilution method and E-test procedure - Serefko, Anna; Malm, Anna (Archives of Medical Science, 2009)
Introduction: Candida albicans still remains the prevailing fungal opportunistic pathogen responsible for serious mucosal and invasive infections. The efficacy of conventional antifungal drugs is becoming limited since several mechanisms of resistance developed by C. albicans have been described. We assessed in vitro activity of caspofungin – an inhibitor of (1,3)-b-glucan synthase – against C. albicans isolates and compared the results obtained by two different methods. Material and methods: The in vitro activity of caspofungin against 96 C. albicans isolates was obtained from the nasopharynx of hospitalised and ambulatory patients assessed using both the reference Clinical Laboratory Standards Institute (CLSI) microdilution method and the E-test procedure. The Kappa test was used in order to calculate the degree of agreement between the outcomes obtained by two different methods. Results: The microdilution and E-test minimal inhibitory concentration values of caspofungin for 90% C. albicans isolates (MICs90) were 0.5 and 0.12 mg/l, respectively. The minimal fungicidal concentration value of caspofungin for 90% C. albicans isolates (MFC90) was 1 mg/l. The outcomes obtained by the E-test procedure exhibited a very good correlation with those achieved by the recommended method as the agreement between MICs within ±2 dilutions read by these two techniques was 88% and the Kappa coefficient was 0.88. Conclusions: Caspofungin demonstrated an excellent potency against C. albicans isolates and the E-test method appears to be useful for determination of in vitro caspofungin activity against these pathogens.